Pengaruh Corporate Social Responsibility Terhadap Kesejahteraan Hidup Masyarakat - Rafiandi, Qasthari Aslan; Amin, Moh.; Sari, Arista Fauzi Kartika (e_Jurnal Ilmiah Riset Akuntansi, 2024)
The aim of this research is to evaluate whether Corporate Social Responsibility (CSR) has an impact on people's lives. This research adopts a quantitative approach, utilizing primary data. The purposive random sampling method was applied to obtain data randomly based on predetermined criteria, involving 212 respondents. The research results show that CSR has a significant positive influence on community welfare. Several indicators contributing to this influence include Corporate Social Responsibility Goals, Corporate Social Issues, and Corporate Relations Programs. These findings underscore the importance of companies committing to CSR initiatives that not only focus on sustainability and social responsibility but also make a tangible contribution to improving the quality of life within communities.Keywords: Corporate Social Responsibility, community welfare, corporate social issues